1985
DOI: 10.1007/bf00698298
|View full text |Cite
|
Sign up to set email alerts
|

Cortical atrophy in senile dementia of the Alzheimer type is mainly due to a decrease in cortical length

Abstract: A prospective study was undertaken to select mentally normal old subjects and patients with senile dementia of the Alzheimer type (SDAT). The test score of Blessed et al. (1968) (BTS) was used to determine the severity of mental impairment. A pathologic study confirmed the diagnosis of either SDAT or normal brain aging at postmortem examination in 12 cases. The cortical area and the cortical perimeter of the different cerebral lobes were measured on 1-cm-thick coronal sections using a semiautomatic image analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 6 publications
3
18
0
Order By: Relevance
“…Our rationale to approximate 2-D tissue shrinkage as a correlate of cortical ribbon length reduction is in agreement with an early study by (Duyckaerts et al, 1985) which demonstrated that the atrophy occurring in the temporal cortex in Alzheimer's disease was a consequence of the decrease in the length of the cortical ribbon, rather than from a reduction in cortical thickness (depth).…”
Section: Assessment Of Shrinkage Artefacts In the Cortex Of Stg And Msupporting
confidence: 83%
“…Our rationale to approximate 2-D tissue shrinkage as a correlate of cortical ribbon length reduction is in agreement with an early study by (Duyckaerts et al, 1985) which demonstrated that the atrophy occurring in the temporal cortex in Alzheimer's disease was a consequence of the decrease in the length of the cortical ribbon, rather than from a reduction in cortical thickness (depth).…”
Section: Assessment Of Shrinkage Artefacts In the Cortex Of Stg And Msupporting
confidence: 83%
“…By contrast, in the parahippocam pal cortex and white matter, the density of SRIF-and NPY-posilive perikarya was similar in the two groups of subjects and was associated with a slight nonsignificant decrease in the total number of SRIF and NPY cell bod ies. In the brains of patients with AD, morphometrical analysis showed a global atrophy (40%) of the parahippo campal cortex (table 2) in agreement with the selective frontotemporal atrophy in the brains of patients with AD [67][68][69][70][71], In contrast, the hippocampus showed no coronal atrophy but only a 30% rostrocaudal narrowing (table 2). Therefore, the increased density of SRIF and NPY neu rons in the hippocampus may be a consequence of the atrophy of the structure, and suggests that the total num ber of neuronal cell bodies is preserved in pathological brains.…”
Section: Srif and Npy Invmmocytochemistry In Brains Of Patients With Adsupporting
confidence: 62%
“…U sing point c ounting, H ubba rd and Anderson [69] found globa l c ortic al atrophy in younger A lzheimer's pa tients, wheras in olde r patients (> 80 ye ars) only the temporal lobe wa s affec ted c ompared to agema tc hed c ontrol persons. Duyc kae rts et al [70], using an image ana lyzing sys te m, me asure d c ortic al area and perimete r, and from the se me as ure me nts c alc ulate d cortical length and me an thic kne ss . In this study there w as a se lec tive atrophy of the temporal c ortex in A lzheimer's pa tients, whic h w as attributed to a de creas e in cortica l length rather than to a de creas e in cortica l thicknes s. Brun and Englund [71] ma ppe d diffe rent cortica l are as in A lzheimer's dise ase a nd re porte d a c ons is tent and ela borate patte rn of atrophy w ith c lea r-cut regional diffe rence s. Be sides ba sa l medial temporal limbic are as , the de ge neration involved the pos terior c ingulate gyrus and s uperior parietal lobule in pa rticular, with les s marke d c ha nge s in the inferior pa rieta l lobule a nd infe rior temporal gyri.…”
Section: Volumementioning
confidence: 99%